P2-S8.04 GYT (Get Yourself Tested) campaign: getting young people talking and tested and sparking a social movement. (10th July 2011) - Friedman, A; Habel, M; Kachur, R; McFarlane, M; Williamson, L; Mishel, M; Levine, S; Binns, A; Kapsimalis, C; Patel, A
Abstract : Background: About 19 million new STDs occur each year in the USA, almost half of which are among youth. Lack of information, misconceptions and stigma prevent many from getting tested. To normalise conversations around sexual health and destigmatize testing, the GYT Campaign was launched in April 2009, with the goal of promoting STD testing among youth ages 15–25 years. Methods: GYT was developed as part of It's Your (Sex) Life, a public information partnership of MTV and the Kaiser Family Foundation, together with the Centers for Disease Control and Prevention and Planned Parenthood Federation of America (PPFA). The campaign uses on-air, online, on-the-ground, and mobile components to increase STD testing and spark an empowering youth movement. It has expanded each year, reaching over 4, 000 health centers nationwide, including school- and college-based health centers. Efforts to evaluate the campaign's reach and impact include media/materials tracking, national surveys, patient intake surveys at partnering clinics and schools, and the monitoring of STD test/positivity rates. Results: At campaign launch, GYT was among the most-searched terms on Google, the most-tweeted terms on Twitter, and the most discussed videos on YouTube. As of January 2010, GYT had produced >60 public service ads and original programs, airing 3200 times on MTV stations (18 h of airtime), and had 1.5 million visitors to www.itsyoursexlife.com . A national survey suggests that campaign awareness among teens (13–19 years; n=766) reached 18% in 2010, with 10–20% reporting that they talked to a friend (21%), family member (18%), partner (11%) or provider (17%) about STDs/testing; and 10% reporting having visited a doctor as a result of the campaign. Available data from participating PPFA clinics revealed a 71% increase in patients presenting for STI testing from April 2008 (pre-campaign) to April 2010, with a 25% increase from April 2009–2010. Chlamydia positivity was 6% among women and 9% among men during campaign promotion periods, indicating that GYT did not simply motivate the worried well. Conclusions: Research suggests that GYT is effectively reaching youth and impacting sexual-health discussions and STD-testing behaviours. The public-private partnership may serve as a model for other sexual health promotion programs. Creative ways for mobilising youth and lessons learnt about campaign branding, celebrity recruitment, and evaluation will be shared.